Tempos escolares e qualidade da educação na legislação: uma incursão pela história - Santos, Fabiano Pereira dos (Universidade Federal de São Carlos, 2021)
From the study of educational legislation from a historiographical point of view, we analyzed the relationship between school time and the quality of education, using historical-dialectical materialism as a theoretical-methodological basis. From the qualitative and quantitative approaches, we try to answer the following problem: why do school times vary throughout the history of Brazilian education? We supported our analysis in the categories school start and end time, schooling time and time at school proposed by Parente (2010; 2006) and identified the (re)emergence of a fourth category: “time corresponding to school”. We used the studies by Dourado and Oliveira (2009), Gadotti (2013) and Soares (2016) to reflect on school times and the quality of education announced in the educational legislation, in particular Law 9.394/1996, in order to understand the motivations for changes in school times and their relationship with the social quality of education. This dissertation is structured in four chapters, which discuss the following: (i.) School times and the quality of education, which serves as a guide for our reflections in the two subsequent chapters; (ii.) the construction of school times in educational legislation from the Colonial period to the First Republic; (iii.) the consolidation of the school days of the Vargas Era until the year 2020; (iv.) the analysis methodology and the results of our research. Given this path, we realize that the category time corresponding to school in the year 2021 results from the use of TDIC, but that its past dates to the Jesuits' time when study times were factors of distinction, inequality and social discrimination. In the end, this research is justified by presenting the historicity of education based on educational legislation, and the transformation of school times is related to educational concepts, principles and purposes. Supposed in educational practices, we recognize “time corresponding to school” as a possibility to improve the quality of education, but we warn of the need to prevent the risks of its use, justifying the search for the hegemonic quality of education.
School times and quality of education in legislation: a foray into history
Keywords: Legislação Escolar; Tempos Escolares; Qualidade da Educação; School Legislation; School Times; Quality of Education; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM